Stationary-Phase Persisters to Ofloxacin Sustain DNA Damage and Require Repair Systems Only during Recovery - Katherine G. Völzing; Mark P. Brynildsen (mBio, 2015)
ABSTRACT Chronic infections are a serious health care problem, and bacterial persisters have been implicated in infection reoccurrence. Progress toward finding antipersister therapies has been slow, in part because of knowledge gaps regarding the physiology of these rare phenotypic variants. Evidence shows that growth status is important for survival, as nongrowing cultures can have 100-fold more persisters than growing populations. However, additional factors are clearly important, as persisters remain rare even in nongrowing populations. What features, beyond growth inhibition, allow persisters to survive antibiotic stress while the majority of their kin succumb to it remains an open question. To investigate this, we used stationary phase as a model nongrowing environment to study Escherichia coli persistence to ofloxacin. Given that the prevailing model of persistence attributes survival to transient dormancy and antibiotic target inactivity, we anticipated that persisters would suffer less damage than their dying kin. However, using genetic mutants, flow cytometry, fluorescence-activated cell sorting, and persistence assays, we discovered that nongrowing ofloxacin persisters experience antibiotic-induced damage that is indistinguishable from that of nonpersisters. Consistent with this, we found that these persisters required DNA repair for survival and that repair machinery was unnecessary until the posttreatment recovery period (after ofloxacin removal). These findings suggest that persistence to ofloxacin is not engendered solely by reduced antibiotic target corruption, demonstrate that what happens following antibiotic stress can be critical to the persistence phenotype, and support the notion that inhibition of DNA damage repair systems could be an effective strategy to eliminate fluoroquinolone persisters. IMPORTANCE In the absence of resistant mutants, infection reoccurrences can still occur because of persisters, rare bacterial cells that survive antibiotic treatments to repopulate infection sites. Persister survival is attributed to a transient state of dormancy in which a cell's growth and metabolism are significantly reduced and many essential processes are thought to be inactive. Thus, dormancy is believed to protect persisters from antibiotic-induced damage and death. In this work, we show that in nongrowing populations, persisters to ofloxacin experience the same level of antibiotic-induced damage as cells that succumb to the treatment and that their survival critically depends on repair of this damage after the conclusion of treatment. These findings reveal that persistence to ofloxacin is not engendered solely by reduced antibiotic target corruption and highlight that processes following antibiotic stress are important to survival. We hypothesize that effective antipersister therapies may be developed on the basis of this knowledge.